Fenomena Perilaku Psikopat Dalam Novel Heartbeat Karya Jealoucy: Kajian Psikologi Sastra - Nurizkia Nabila; Yurza Aina Zia Ulhaq; Eva Dwi Kurniawan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
In recent years, there has been an alarming increase in crime cases in Indonesia, sometimes linked to psychiatric symptoms. Psychosis is a form of mental disorder characterized by a lack of personal organization and integration, an inability to take moral responsibility, and frequent conflicts with social norms and laws due to illness.mental, created by your own imagination.This study aims to describe the phenomenon of psychopathic behavior in Jealoucy's novel Heartbeat using a literary psychology approach, specifically using Sigmund Freud's theory of psychopathic personality disorder.Basically, literary psychology deals with the psychology of fictional characters in literary works. The data analysis technique used is a qualitative descriptive technique. Based on the results of several studies, it can be seen that (1) the psychopathic behavior of the characters in Jealoucy's novel Heartbeat is known to be based on specific behavioral characteristics of psychopaths, specifically, their penchant for manipulation and action. aggressive, brutal behavior, without remorse or guilt, capable of recognizing forms of psychopathic behavior divided into 3 types: mild, moderate and severe. (2) The factors that cause the characters in the novel Heartbeat to have psychopathic behaviorare genetic factors and environmental factors.